2019
DOI: 10.1155/2019/3725863
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Angiogenic Potential of Human Regulatory Macrophages (Mreg) after Ischemia/Reperfusion Injury In Vitro

Abstract: Ischemia/reperfusion- (I/R-) induced organ damage represents one of the main causes of death worldwide, and new strategies to reduce I/R injury are urgently needed. We have shown that programmable cells of monocytic origin (PCMO) respond to I/R with the release of angiogenic mediators and that transplantation of PCMO results in increased neovascularization. Human regulatory macrophages (Mreg), which are also of monocytic origin, have been successfully employed in clinical transplantation studies due to their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Thus, the role of Klf4 is determined by different genes interacting with Klf4. Hummitzsch et al [21] found that the expression level of Klf4 was decreased in Human Regulatory Macrophages after H/R. Meanwhile, Klf4 could alleviate lipopolysaccharide-induced in ammation and cerebral vascular injury after cerebral ischemic stroke [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of Klf4 is determined by different genes interacting with Klf4. Hummitzsch et al [21] found that the expression level of Klf4 was decreased in Human Regulatory Macrophages after H/R. Meanwhile, Klf4 could alleviate lipopolysaccharide-induced in ammation and cerebral vascular injury after cerebral ischemic stroke [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, tube formation assays utilizing human umbilical vein endothelial cells (HUVEC) were performed to estimate the pro-angiogenic capacity of RIPC/cRIPC plasma and cell culture supernatants derived from RIPC/ cRIPC treated human monocytes. Although in-vitro tube formation assays do not fully resemble all aspects of in-vivo angiogenesis, they have been used by several groups and represent a reproducible and stable system for the in-vitro analysis of early processes of angiogenesis [3,22,23,42]. Employing in-vitro tube formation assays in combination with computer-assisted analysis [4], several parameters of angiogenesis were significantly increased by RIPC/cRIPC plasma.…”
Section: Effects Of Ripc/cripc Plasma and Supernatants Derived From Ripc/cripc Monocytes On In-vitro Angiogenesismentioning
confidence: 99%
“…Therefore, so-called programmable cells of monocytic origin (PCMO) and regulatory macrophages (Mreg) have been described as promising cell types for transplantation into ischemic tissues [ 17 ]. Both cell types can be generated from leukapheresis products and cultured similarly with macrophage colony-stimulating factor (M-CSF) and interleukin 3 (Il-3), respectively, with interferon (IFN) γ [ 18 , 19 ]. PCMO and Mreg were designed to overcome the obstacles of ischemic microenvironment showing a robust phenotype in ischemia/reperfusion in vitro experiments and enhanced pro-angiogenic potential by paracrine secretion of macrophage inflammatory protein α (MIP-1 α), granulocyte-macrophage colony-stimulating factor (GM-CSF), pentraxin-related protein 3 (PTX 3), and monocyte chemoattractant protein-1 (MCP-1) in vitro and in vivo studies [ 17 , 18 , 19 ].…”
Section: Cell Priming Of Cell Products Prior To Transplantationmentioning
confidence: 99%
“…Both cell types can be generated from leukapheresis products and cultured similarly with macrophage colony-stimulating factor (M-CSF) and interleukin 3 (Il-3), respectively, with interferon (IFN) γ [ 18 , 19 ]. PCMO and Mreg were designed to overcome the obstacles of ischemic microenvironment showing a robust phenotype in ischemia/reperfusion in vitro experiments and enhanced pro-angiogenic potential by paracrine secretion of macrophage inflammatory protein α (MIP-1 α), granulocyte-macrophage colony-stimulating factor (GM-CSF), pentraxin-related protein 3 (PTX 3), and monocyte chemoattractant protein-1 (MCP-1) in vitro and in vivo studies [ 17 , 18 , 19 ]. Moreover, cell lines from monocytic origin may provide further cellular features that could also support or induce tissue regeneration due to the reparative capabilities and phagocytic activity of mononuclear cells.…”
Section: Cell Priming Of Cell Products Prior To Transplantationmentioning
confidence: 99%
See 1 more Smart Citation